Problem based curricula and problem based learning in physiotherapy: A critical review - C. A. Eksteen; J. A. Slabbert (AOSIS, 2001)
Introduction: Problem based curricula and problem based learning are used extensively to facilitate learners to become effective learners and through that, effective professional problem solvers. The basic characteristics of the problem based curriculum and the processes of the problem based learning are described in the literature but many variations of problem based learning and the problem based curriculum exist. Research findings are also contradictory regarding the effectiveness of these approaches. The aim of this article is to discuss the theoretical foundation of these approaches and to identify the core issues that must be addressed in order to optimize their effect on learners. Methodology: A literature search was done by using the following keywords: problem based curriculum, problem based learning, clinical decision making, clinical problem solving, clinical judgement, physiotherapy, medicine, health care, and health care education. Discussion: There is a lack of research in the literature that shows evidence that the problem based curricula and problem based learning is more beneficial for students' learning or mastering specific competencies than learning in a traditional curriculum. Papers on problem based curriculum and problem based learning describe the process and state the desired effects of the teaching approaches without explicitly describing the contextual and transactional environments, as well as the internal (departmental) environment in which the change in teaching approach took place and how it was adapted to their situation. Furthermore, no research could be found on ways to address the negative outcomes of problem based learning. There is thus a need for well designed research protocols to show the best evidence of physiotherapy educational practice.